Zimbabwe's dryland research station - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A crops specialist and a livestock specialist from the Matopos research station describe technologies being developed to support smallholder farmers experiencing drought